Semi-fragile video watermarking algorithm for H.264/AVC based on cost strategy - Wei-wei ZHANG; Chen ZHAO; De-tian HUANG; Pei ZHANG; Yi-xian YANG (Tongxin xuebao)
In order to solve some existing problems on detecting malicious tampering by video watermarking based on H.264/AVC video compression standard,a semi-fragile video watermarking algorithm for H.264/AVC based on cost strategy was proposed.To further improve the robustness of the feature codes in semi-fragile video watermarking algorithm,a new generation algorithm for feature codes by eliminating the correlation of them was proposed.In order to meet the requirement that the semi-fragile watermarks should be uniformly embedded into the video frames to locate the tampered region accurately,a minimal cost function was introduced to select a DCT coefficient in the 4 × 4 block residual to embed watermark which had minimal impact on the video quality and bit rates.Experimental results show that the proposed algorithm can significantly reduce impact on video quality and bit rate because of embedding the watermarking by adopting the minimum cost function and it is sensitive to malicious manipulations.The retrieved feature code and watermarking can detect and locate malicious manipulations.